JOURNALISM FOR SUSTAINABLE TOURISM: A POLITICAL ECONOMY DISCOURSE OF WEST NUSA TENGGARA LOCAL MEDIA ON THE RINJANI ECOTOURISM ISSUES - Aurelius Rofinus Lolong Teluma; Muhammad Jamiluddin Nur; Muhlis (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
The practices of eco-journalism in West Nusa Tenggara local media have not been sufficient in journalistic performance in favor of environmental sustainability. This study aims to describe and analyze the news construction of West Nusa Tenggara or NTB local media in reporting the Mount Rinjani ecotourism industry during 2020. The study focuses on describing the pattern of power relations between the political-economic components of the West Nusa Tenggara local media institutions in reporting the issue of the Rinjani ecotourism business developments. The method used in this research is a case study. Using media-political analysis of news construction and the dynamics of power relations, the data were analyzed. Data collection uses related news clippings and in-depth interviews. The results show that in terms of quantity, the contents of Suara NTB, Lombok Post, and Kicknewstoday.com do not make Rinjani Ecotourism be the central issue in daily news headlines. Meanwhile, on the side of the discourse aspect, West Nusa Tenggara local media tend to describe government policies about Rinjani ecotourism as they are normal. West Nusa Tenggara local media lack in providing the news with critical notes on various aspects of Rinjani’s ecotourism development. In addition, the results of the political-economic analysis reveal that the West Nusa Tenggara local media structurally tend to build a synergy of power with the local government regarding the development of Rinjani ecotourism.